Analisis Barang Bukti Pada Aplikasi Whatsapp Menggunakan FTK Imager Di Kelas Teknik Komputer Universitas Bina Darma - Dasmen, Rahmat Novrianda; Fikri, Muhammad; Rasmila, Rasmila; Tritama, Habib Elfariz; Aulia, Muhammad Rizky; Saputra, Kms. M. Okta Agung (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 13 No 2 (2024): JELIKU Volume 13 No 2, November 2024DO - 10.24843/JLK.2024.v13.i02.p09, 2024)
The advancement of technology has both positive and negative effects, including increased communication ease and the rise of cyberbullying, particularly affecting children and young people. This study analyzes the impact of WhatsApp, a popular communication tool in Indonesia, on cyberbullying. This study develops a forensic scenario for cyberbullying, focusing on WhatsApp applications. Researchers identify the perpetrator and create a digital group member using a flashdisk. The findings are used to improve research design, forensic techniques, and legal aspects. The study uses FlashDisk and FTK Imager forensic tools to identify cyberbullying images. It involves collection, examination, and analysis of images with various sizes, filenames, and widths. The report provides an analysis and a detailed report on the findings. The study uses forensic data to analyze cyberbullying images in a chat group using FTK Imager. Data is collected and analyzed using three steps: collection, processing, and storage. The results show two cyberbullying image images using NIST methodology, suggesting that further research could use other forensic methods